Cluster Component of Sustainable Regional Development: Romanian Practice and Ukrainian Realities - Liashenko, V.; Trushkina, N. (Економічний вісник Донбасу, 2021)
At present, the problems of improving the management of cluster structures in the economic regions of Ukraine, taking into account the best Romanian experience in accordance with modern challenges related to smart specialization, modernization of production and digitalization of organizational and managerial processes, are especially relevant. For the further development of clusters in Romania it is necessary to develop a set of measures, namely: stimulating exports through internationalization; formation of fundamentally new value chains integrated into vertical industries; business strategy; assistance in financing innovative projects for technology transfer based on the mechanism of public-private partnership and with the involvement of private investment; use of cluster management tools; developing tools that can support efficient resource allocation processes among cluster members; training; formation of proper organizational culture. The implementation of these measures should be carried out with the help of the European Cluster Cooperation Platform and the European Cluster Improvement Program, the EU Action “Cluster Go International”, and the Eurocluster Program for the period 2021-2027. Based on the generalization of the best Romanian experience, it is established that in order to increase the competitiveness of national and regional economies, it is necessary to create cluster structures as effective forms of partnership. However, the study revealed that the current legislation of Ukraine does not pay due attention to the formation and functioning of clusters. To do this, it is necessary to make changes and additions to the Concept of creating clusters in Ukraine, Regional Development Strategies until 2027, and Action Plans for their implementation for 2021-2023 to create cluster structures as a business entity. It is expedient to develop and approve the Concepts of cluster policy and the Target Program “Formation and development of clusters in the regions of Ukraine for 2021-2023”, which should provide for the creation of clusters as a special type of enterprise association in various fields and taking into account regional specifics.